2006
DOI: 10.5172/conu.2006.21.1.32
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial testing the impact of exercise on cognitive symptoms and disability of residents with dementia

Abstract: A randomized controlled trial was undertaken to measure effects of exercise on: 1) the progression of cognitive symptoms related to dementia using the Clock- Drawing test Shulman et al. 1993); and 2) disability using the Revised Elderly Persons Disabilities Scale (REPDS; Fleming and Bowles 1993). Data was analysed from 75 nursing home residents with dementia who were randomly assigned to one experimental group and two control groups. Group 1 (control) received no intervention, Group 2 (control) received a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 9 publications
2
119
1
2
Order By: Relevance
“…recent Cochrane Review concluded that exercise studies on neuropsychiatric symptoms, which were able to show a similar effect, were of insufficient quality [9] though, in that review, some previous low intensity or multimodal intervention studies were suggestive that exercise improved neuropsychiatric symptoms [31,32]. Our findings indicate that physical exercise may inhibit or delay the emergence of more severe neuropsychiatric symptoms with disease progression.…”
Section: Discussionmentioning
confidence: 66%
“…recent Cochrane Review concluded that exercise studies on neuropsychiatric symptoms, which were able to show a similar effect, were of insufficient quality [9] though, in that review, some previous low intensity or multimodal intervention studies were suggestive that exercise improved neuropsychiatric symptoms [31,32]. Our findings indicate that physical exercise may inhibit or delay the emergence of more severe neuropsychiatric symptoms with disease progression.…”
Section: Discussionmentioning
confidence: 66%
“…All studies used randomization, but only seven of them described that treatment allocation was concealed (NCD 31, 35 and CD 41,42,[46][47][48] ). Despite randomization, groups were not comparable at baseline in five studies (NCD 28, 30, 33 and CD 45,46 ).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Despite randomization, groups were not comparable at baseline in five studies (NCD 28, 30, 33 and CD 45,46 ). In five of the 17 studies reporting that study groups were similar at baseline, the number of participants per group was only fifteen or less (NCD 29, 34, 39 and CD 41,48 ), which complicates finding statistically significant between-group differences.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…One study reported on participants with severe AD [27], and two studies reported on participants with a range of severe-to-mild AD [28,29]. Three reports included participants with moderate-to-mild dementia [30][31][32], three studies reported on individuals with amnestic MCI and mild dementia [33][34][35], and one study reported on participants with a range of moderate-tomild cognitive impairment and mild dementia [36]. One study reported on individuals with a range of moderate-to-mild cognitive impairment [37], another study reported on participants with MCI and mild dementia [38], and two reported on individuals with MCI only [39,40].…”
Section: Resultsmentioning
confidence: 99%